FOSSIL FLORAS IN THE COLLECTIONS OF THE GEOLOGICAL MUSEUM OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV - Nesterovskyi, V.; Vakulenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Collection of flora in the Geological museum (Taras Shevchenko National University of Kyiv) is a great taxonomic variety of things and finds from different localities in Ukraine and other countries. Florristic rests have different geological age. Collection presents an evolution of flora on the Earth, has good preservation and remarkable prints of the differents parts of plants.